Mutluluk ekonomisi ve göç üzerine bir inceleme - Gül, Songül (My University, 2017)
MUTLULUK EKONOMİSİ VE GÖÇ ÜZERİNE BİR İNCELEME Günümüzün ana akım iktisat anlayışı olan neoklasik iktisat, insanı toplumsal bir varlık olarak görmemekte, bireyi içinde doğup büyüdüğü toplum ve o toplumu oluşturan sendika, grup, dini cemaat, etnik kimlik, politik görüş gibi faktörler ile bireye ait genetik faktörler, yaş, cinsiyet vb. gibi sosyo-demografik özelliklerden ayrı tutmaktadır. Bu nedenle neoklasik iktisatta toplumun yaşam memnuniyeti mutlak gelir gibi objektif iktisadi parametrelerle ölçülmektedir. Ancak neoklasik iktisada yönelen eleştiriler sonucunda ortaya çıkan davranışsal iktisat disiplininin alt dalı olarak gelişen mutluluk ekonomisi çalışmaları; toplumun yaşam memnuniyeti üzerinde, mutlak gelir gibi objektif iktisadi parametreler dışında bireye ve içinde yaşadığı topluma ait birçok değişkenin etkili olduğunu göstermektedir.Bu tezde iktisadi parametrelerin tek başına yaşam memnuniyetini açıklamadaki yeterliliği “Türkiye’de yaşayan göçmenler” örneği üzerinden tespit edilmeye çalışılmış ve aynı zamanda Türkiye'de yaşayan göçmenlerin yaşam memnuniyeti üzerinde bir durum tespiti yapılmıştır. Mutluluk, yaşam memnuniyeti, göç, kurumlar

AN EXAMINATION ON HAPPINESS ECONOMY AND MIGRATION Recently, mainstream economics is dominated by neoclassical economics, does not view individuals as social beings. As such, it dissociates an individual from factors such as the society in which s/ he lives and unions, groups, religious associations, ethnic identity, political views, which altogether making of the society, as well as from socio-demographic characteristics such as genetic factors, age, gender etc., which belong to the individual. Therefore, in neoclassical economics, life contentment of the society is measured through objective economic parameters, e.g. absolute income. However, happiness economics studies, which developed as a branch of behavioral economics, which emerged as a result of criticisms against neoclassical economics, have shown that in a society’s life contentment, apart from objective economic parameters such as absolute income, many different variables that belong to the individual and the society are effective. The dissertation aimed to evaluate the adequateness of economic parameters per se in explaining life contentment through the example of ‘the immigrants in Turkey’ and at the same time to determine life contentment of immigrants in Turkey. Happiness, life satisfaction, migration, institution
Keywords: Ekonomi; Göç; Psikolojik yönler; Türkiye